The Effect Of Cake Application On Students’ Vocabulary Mastery At Eighth Grade Of Smp Negeri 12 Pematangsiantar - Simatupang, Gracia Elizabeth; Maria Efipanias Manihuruk, Leonita; Siahaan, Basar Lolo (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This study investigates the effect of the Cake Application on eighth-grade students’ mastery of action verbs in recount texts at SMP Negeri 12 Pematangsiantar. Motivated by students’ low vocabulary performance, especially in understanding the linguistic features of recount texts as required by the Merdeka Curriculum (Permendikbud No. 5 of 2022), this research employs a quasi-experimental design. Two classes were assigned as control and experimental groups. The experimental class received instruction through the Cake Application, while the control class used conventional media. Pre-test and post-test scores show a significant improvement in the experimental class (from 55.9 to 77.74). Independent t-test results (t = 3.854, p < 0.001) confirm the effectiveness of the treatment. These findings suggest that Cake Application significantly enhances students’ vocabulary mastery, particularly in action verbs relevant to recount texts.